Resistência genética à infestação natural e artificial por Rhipicephalus (Boophilus) microplus em bovinos das raças Hereford e Braford - Biegelmeyer, Patrícia (2012)
The overall aim of this study was to analyze different perspectives of Rhipicephalus (Boophilus) microplus genetic resistance. Therefore, the present study was divided into three manuscripts. Firstly, a literature review was conducted to present some aspects of tick resistance, like results of previous studies of bovine resistance, environmental effects on this triat, and some findings in molecular biology that will help to identify resistant animals. The second trial was conducted to estimate genetic parameters for tick resistance measured by two assessment methods in Hereford and Braford cattle, and genetic correlations between tick resistance and growth of animals. The animals belonging to the Delta G Connection genetic improvement consortium, were raised on nature and artificial pastures in Southern Brazil, and the age at the evaluation period was about 18 months. Data were analyzed from 6,462 bovines naturally exposed to ticks. The number of ticks was counted at inner hind legs region (IHL) of 3,413 animals between 2001 and 2008, and was recorded up to three consecutive counts at one side of body (LAT) in 3,049 bovines between 2009 and 2010, a total of 7,813 records. In addition, the database contained data of 109,566 birth weights (BW), 112,815 records of weight gain from birth to weaning (ADG) and 54,843 data of weight gain from weaning to yearling (PWG). For the analyses, tick count data was transformed using a logarithmic function. Heritability estimates obtained by bivariate analysis were IHL = 0.152 ± 0.043 and LAT = 0.235 ± 0.063 and genetic correlation between both methods was 0.575 ± 0.220. Single-trait analysis of LAT indicated a repeatability of 0.312 ± 0.014. Genetics association analysis between IHL and LAT and the development characteristics evaluated indicated significant associations between IHL and BW (0.220 ± 0.102), and favorable negative correlations between LAT and ADG (-0.211 ± 0.099) and LAT and PWG (-0.650 ± 0.125) (P<0.05). The objective of third trial was to analyze the bovine genetic resistance effect on tick biological traits. The engorged female ticks analyzed were collected from 40 Braford heifers classified as genetically resistant (R) or susceptible (S), according to the breeding values for tick count, calculated based on a database with 9,036 records of Hereford and Braford bovines. After classification, the selected heifers were moved to an experimental area in Embrapa Pecuária Sul, located in the city of Bagé, in the Brazilian state of Rio Grande do Sul, and subjected to four artificial infestations, 14 days apart each one. Weights of engorged female ticks and of female ticks after oviposition did not differ between resistant and susceptible heifers. Female ticks engorged in genetically susceptible heifers showed higher capacity of posture (R = 0.097 ± 0.021g and S = 0.109 ± 0.030g) and higher values of reproductive efficiency index (R = 47.23 ± 5.85% and S = 53.27 ± 3.74%) The overall aim of this study was to analyze different perspectives of Rhipicephalus (Boophilus) microplus genetic resistance. Therefore, the present study was divided into three manuscripts. Firstly, a literature review was conducted to present some aspects of tick resistance, like results of previous studies of bovine resistance, environmental effects on this triat, and some findings in molecular biology that will help to identify resistant animals. The second trial was conducted to estimate genetic parameters for tick resistance measured by two assessment methods in Hereford and Braford cattle, and genetic correlations between tick resistance and growth of animals. The animals belonging to the Delta G Connection genetic improvement consortium, were raised on nature and artificial pastures in Southern Brazil, and the age at the evaluation period was about 18 months. Data were analyzed from 6,462 bovines naturally exposed to ticks. The number of ticks was counted at inner hind legs region (IHL) of 3,413 animals between 2001 and 2008, and was recorded up to three consecutive counts at one side of body (LAT) in 3,049 bovines between 2009 and 2010, a total of 7,813 records. In addition, the database contained data of 109,566 birth weights (BW), 112,815 records of weight gain from birth to weaning (ADG) and 54,843 data of weight gain from weaning to yearling (PWG). For the analyses, tick count data was transformed using a logarithmic function. Heritability estimates obtained by bivariate analysis were IHL = 0.152 ± 0.043 and LAT = 0.235 ± 0.063 and genetic correlation between both methods was 0.575 ± 0.220. Single-trait analysis of LAT indicated a repeatability of 0.312 ± 0.014. Genetics association analysis between IHL and LAT and the development characteristics evaluated indicated significant associations between IHL and BW (0.220 ± 0.102), and favorable negative correlations between LAT and ADG (-0.211 ± 0.099) and LAT and PWG (-0.650 ± 0.125) (P<0.05). The objective of third trial was to analyze the bovine genetic resistance effect on tick biological traits. The engorged female ticks analyzed were collected from 40 Braford heifers classified as genetically resistant (R) or susceptible (S), according to the breeding values for tick count, calculated based on a database with 9,036 records of Hereford and Braford bovines. After classification, the selected heifers were moved to an experimental area in Embrapa Pecuária Sul, located in the city of Bagé, in the Brazilian state of Rio Grande do Sul, and subjected to four artificial infestations, 14 days apart each one. Weights of engorged female ticks and of female ticks after oviposition did not differ between resistant and susceptible heifers. Female ticks engorged in genetically susceptible heifers showed higher capacity of posture (R = 0.097 ± 0.021g and S = 0.109 ± 0.030g) and higher values of reproductive efficiency index (R = 47.23 ± 5.85% and S = 53.27 ± 3.74%)